Post-shingles granulomatous dermatosis related to anti-programmed cell death 1. (28th March 2019) - Assi, Tarek; Danu, Alina; Mateus, Christine; Robert, Caroline; Michot, Jean-Marie; Ibrahim, Tony; Lazarovici, Julien; Ghez, David; Rossignol, Julien; Dartigues, Peggy; Terroir-Cassou-Mounat, Marie; Ribrag, Vincent
The most recent progress in the oncology field has led to a paradigm shift in the management of cancer with the tsunami of immune checkpoint inhibitors that are associated with a particular pattern of immunological adverse events. This is a case of a 54-year-old woman that demonstrated a granulomatous reaction in the same dermatomal distribution of a previously treated shingles infection during treatment with an anti-programmed death 1 agent (pembrolizumab) for a newly diagnosed stage IV Hodgkin lymphoma. The purpose of this case is to increase the awareness of oncologists dealing with a new pattern of side effects taking into account the patient's background and recent exposures to latent viruses such as herpes zoster to prevent unnecessary diagnostic and therapeutic measures.